PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI YAYASAN PENDIDIKAN KELING KUMANG - Veronika Lidia; Dewi Sara; Riska Juliarsih (Jurnal Bisnis dan Kewirausahaan, 2023)
This research aims to determine the influence of organizational culture and work discipline on the performance of Keling Kumang Education Foundation employees. The number of samples in this research was 50 employees at the Keling Kumang Education Foundation. This research uses quantitative analysis methods. The results of this research can show that organizational culture and work discipline have a significant influence on the performance of Keling Kumang Education Foundation employees. This is proven by the average value of the influence of organizational culture on employee performance of 22.32 and a standard deviation of 2.199. The average influence of work discipline on employee performance is 21.64 and the standard deviation is 1.987. The average employee performance is 21.28 and the standard deviation is 2,268. The data above shows that the data studied is valid, so the hypothesis is accepted.